Responsabilidad social en el manejo Contable y Financiero de los Gobiernos Autònomos Descentralizados del Ecuador año 2017 caso GADS Parroquiales de la Provincia Bolìvar - Gallegos Vergara, Silvia Alexandra (2017)
With the accomplishment of the present work titled "Social Responsibility in the accounting and financial management of the Decentralized Autonomous Governments of Ecuador-Parish GADs Case of the Bolivar Province, it analyzes in detail the social responsibility of these state institutions with administrative, economic and financial autonomy ; Which are dedicated to improving the conditions of the people, who administer the state funds in works that benefit the community that chose them although in many cases it is seen that those only perform works in specific places of mutual convenience but not in places And more vulnerable and needy people without fulfilling the commitment acquired is therefore the conduct of this research to determine the degree of social responsibility. It also analyzes the economic and financial management of those institutions, for the benefit of the most needy class and if it is carried out according to the Law and to the dispositions of the control organisms that exist. The work contains five chapters very well structured and begins with the respective Background to anticipate the reader of what is going to be discussed, the Framework is the sustenance of theories and thoughts that some authors express on the subject; The Methodological Design covers the method used, the type of research and the instruments to be used; The analysis of the problem contains the diagnosis of what happens in what has to do with social responsibility and with the economic management of the GADs, in particular of the Parochial GADs of the Bolivar Province; Concludes with the conclusions or research results that indicate that the majority of GADs do not fulfill their social responsibility function and that their resources are not well managed due in many cases to the majority of officials and employees are unaware about what is public administration And the proper management of the people's resources.